Safavid Libraries: Continuity and Change in Functions - Mahshid Borjian Borujeni; Zahra Abazari; Gholamreza Amirkhani; Fereshteh Sepehr; Nadjla Hariri (کتابداری و اطلاع‌رسانی)
Objective: The main objective of the research is to study and analyze the function and role of libraries during the Safavid dinasty. Methodology: According to the nature of the research, a library method based on books, manuscripts, and first-hand (primary) documents, has been used. Findings: The present study shows that in general, two distinct periods can be considered in the life and function of Safavid libraries. The first period, which is related to the 16th century and the reign of Shah Ismail and part of the time of Shah Tahmasb, is a continuation of the role and function of the 15th century libraries, especially the Timurid libraries in Khurasan, where the main task of libraries is to produce and create exquisite manuscripts using the highest level of book design arts. The second approach was to pay attention to libraries in the position of preserving and maintaining the written works of Shiite scholars and jurists, which is considered a significant change in the role and function of important libraries of this period. In this regard, a fundamental change took place in Shia jurisprudential-theological texts, most of which were written by scholars who had migrated to Iran from the Jabal Amel region of Lebanon. The transfer of the personal libraries of this group of immigrant scholars caused many Arabic works to be transferred to Iran. In addition to this kind of texts, attention to Persian language as the language of writing jurisprudential-religious works and used by the public is one of the other features of this period. In addition to the necessity of the time and the need of the Safavid government to gain legitimacy and explain the jurisprudence principles of the Shia religion by using the books and treatises that appeared, including authoring, translating, summarizing and rewriting, another factor was also raised, which was: the negative view from some jurisprudential thoughts to the category of painting, which specifically caused Shah Tahmasb to close the art workshop of his royal library in Qazvin. The change of the capital from Qazvin to Isfahan was also formed in a context affected by these developments. In Isfahan, Shah Abbas committed himself to the establishment of the royal library, which was located in the building complex known as Dowlatkhaneh. In addition, he and his great contemporary scholar, Sheikh Bahai, by taking advantage of the tradition of endowment, gave increasing prosperity to the libraries of the holy shrines, which in particular should be the important collections dedicated to the mausoleum of Sheikh Safi in Ardabil and the library of Imam Reza Shrine in Mashhad (Astan-e Quds-e Razavi). Despite the variety of works that later influenced the collection of the Astan-e Quds library, most of the works available in that place and in other libraries of the second Safavid period, were dedicated to religious and jurisprudential texts, which are generally found in the libraries of schools, mosques, and holy shrines or personal collections were kept. Conclusion: The function and position of libraries during Safavid period can be seen in two different ways. In the first, the continuation of the function of the libraries was like the previous period, in which the main task of the libraries was to create exquisite manuscripts by using the well-known painters, calligraphers, and book designers. In the second stage, more attention was paid to libraries as a place to preserve the written works of Shiite scholars and jurists, which is considered a significant change in the role and performance of important libraries of this period.